Kajian Perilaku Pengeringan Sari Buah dengan Pengering Semprot Searah - Ansar Ansar; Suhargo Suhargo; Budi Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
This study aimed to examine the behavior of concurrent spray drying of fruit juice on various inlet temperature of the drying air and atomization air pressure, The temperature of inlet drying air ranged approximately from 115 °C and 135 °C. The atomization air pressures were varied from 1,8593; 1,8746; and 1,9245 Pa. The data of this study consist of predicted and observed data. Observed data obtained from laboratory experiment which included the distribution of drying air temperature as along the axial distances and the average moisture content of final product. Predicted data obtained to simulate models based on three mathematical models consists of mass, momentum, and energy balance equation. The mathematical models were employed to predict the temperature of drying air distribution and the average of moisture content offinal product. The results of the study showed thatj the mathematical models represent of the behavior of fruit juice drying using concurrent spray dryer. On the same material bait; number, size, and droplet distribution were changed on the change of atomization air pressures and air temperature drying. The higher was the atomization air pressure and the air temperature which were used, the greater was the droplet which were product.